Produktivitätsparadoxon der Digitalisierung im Krankenhaus – auf der Suche nach effizienzsteigernden Innovationen - Simon Reif; Theresa Bolz; Yasemin Karamik (Wirtschaftsdienst, 2024)
– The productivity paradox of digitisation in hospitals refers to the difficulty in realising measurable efficiency gains from digital innovations. Despite significant investments, healthcare costs continue to rise, particularly in OECD countries like Germany. While digitisation is expected to enhance efficiency, empirical evidence for substantial productivity improvements remains limited. This study analyses data from the European Hospital Survey and finds no clear correlation between hospitals' digital integration and operational efficiency. It remains uncertain whether current policy efforts to increase health care digitalisation will yield the desired efficiency gains. More robust evidence to identify innovations that genuinely improve healthcare efficiency is needed to avoid cuts to available care for individuals in the social health insurance.
Keywords: I11; I18; O33; 330; Krankenhaus; Digitalisierung; Innovation; Krankenhaus; Digitalisierung; Innovation